Novo normal do trabalho - o direito à desconexão do trabalho em tempos de pandemia de COVID-19 - Lopatiuk, Carlos (2021)
With technological ease, employees and employers can stay connected all day long. The following article addresses these changes that have occurred in recent decades and intensified with the pandemic in relation to telework and HomeOffice modeling. This article addresses the impact on the lives of these workers who lost their right to disconnection and seeks the current legal support so that this right is guaranteed to the worker. The workday containment law, explained in Article 7 of the Federal Constitution, provides for a daily work duration of eight hours, from which time it is stipulated that the worker must earn overtime. Overtime is only allowed two more hours. The non-disconnection significantly attacks the right to not work guaranteed to the worker in law.